Ethyl 3-amino-4-[(2-hydroxyethyl)amino]benzoate - Arumugam, Natarajan; Abdul Rahim, Aisyah Saad; Abd Hamid, Shafida; Rosli, Mohd Mustaqim; Fun, Hoong-Kun (International Union of Crystallography, 2010)
In the crystal structure of the title compound, C11H16N2O3, molecules are linked by one O—H N and two N—H O intermolecular hydrogen bonds into a three-dimensional network, which incorporates R22(14) and R22(16) graph-set motifs.